2011
DOI: 10.1186/1471-2458-11-26
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity behaviours of Culturally and Linguistically Diverse (CALD) women living in Australia: A qualitative study of socio-cultural influences

Abstract: BackgroundAustralia continues to witness rising levels of immigration by individuals from Culturally and Linguistically Diverse (CALD) origins. With this rapidly growing diverse population, Australia faces a number of population health challenges. In particular, CALD women have been shown to be at an increased risk of chronic diseases such as cardiovascular disease, diabetes, and poor mental health. Despite the high risk of these diseases, women from CALD groups are less likely to be proactive in accessing hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
96
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 41 publications
11
96
1
Order By: Relevance
“…Overall, previous physical activity experience [e.g., 44,86] and general health [e.g., 50,87] were positive correlates of physical activity. Lack of good health [72] or having depression had a negative association with physical activity.…”
Section: Psychosocialmentioning
confidence: 97%
See 4 more Smart Citations
“…Overall, previous physical activity experience [e.g., 44,86] and general health [e.g., 50,87] were positive correlates of physical activity. Lack of good health [72] or having depression had a negative association with physical activity.…”
Section: Psychosocialmentioning
confidence: 97%
“…Specifically, a longer time in the country (10yrs +) [39,40], later generations (being born and having parents born in the new country) [41] and citizenship in the new country [42] also suggested an association with higher participation rates. Studies that evaluated reasons for immigration found that refugee populations suffered post-traumatic stress and were not considering or actively participating in physical activity [43,44] . Generally, the type of physical activities performed in the home country predicted physical activities in the new country [43,45,46].…”
Section: Correlatesmentioning
confidence: 99%
See 3 more Smart Citations